Raising the Research Octane Number using an optimized Simulated Moving Bed technology towards greater sustainability and economic return. (1st April 2023) - Muhammed, Tasneem; Tokay, Begum; Conradie, Alex
Graphical abstract: Highlights: A rigorous Simulated Moving Bed (SMB) dynamic model for raising the Research Octane Number of fuel. Operating conditions are optimized using a genetic algorithm to maximize the Research Octane Number and the Gross Margin. SMB can replace outmoded distillation as the separation technology, achieving greater sustainability and economic return. Abstract: The scale of CO2 emissions from light-duty vehicle (LDV) fleets worldwide has led governments to mandate substantive improvements in vehicle fuel economy, thereby mitigating climate change. Raising the Research Octane Number (RON) of fuel through isomerization, alongside mandates to recalibrate existing LDV engines, promises to contribute substantially to climate action. This study has aimed to develop a highly efficient adsorption separation technology for isomerization refining that can contribute significantly to the sustainability and economics of the overall "well-to-wheel" outcome for LDV fleets globally. This study developed a rigorous dynamic model for a Simulated Moving Bed (SMB), comparing the SMB to conventional distillation as the next best alternative. The SMB was optimized using a genetic algorithm, maximizing RON and Gross Margin as objective functions. This study showed that SMB effectively separates high octane components from low octane components, producing a fuel with a RON of 95 when maximizing the RON, thereby enabling lower emissions associated with recalibrated LDV engines. Compared to 11 MW of steam duty associated with conventional distillation, the SMB unit utilized 3.4 MW and 5.7 MW of electricity when optimizing the RON and the Gross Margin respectively, appreciably reducing comparative greenhouse gas emissions. Finally, compared to conventional distillation as measured by Gross Margin, the optimized SMB unit increased the economic return by 47% when maximizing the RON and by 82 % when maximizing the Gross Margin. In summary, this study motivated for rapid capital investment into retrofitting isomerization facilities with SMB unit operations, replacing outmoded distillation as the primary separation technology. Future work will focus on optimizing the separation technology alongside the overall isomerization process using a rigorous techno-economic analysis as the objective function for optimization.